Differential responses to artificial selection on oviposition site preferences in Drosophila melanogaster and D. simulans - Soto, Eduardo Maria (2014)
The preference–performance relationship in plant–insect interactions is a central theme in evolutionary ecology. Among many insects, eggs are vulnerable and larvae have limited mobility, making the choice of an appropriate oviposition site one of the most important decisions for a female. We investigated the evolution of oviposition preferences in Drosophila melanogaster Meigen and Drosophila simulans Sturtevant by artificially selecting for the preference for 2 natural resources, grape and quince. The main finding of our study is the differential responses of D. melanogaster and D. simulans. Although preferences evolved in the experimental populations of D. melanogaster, responses were not consistent with the selection regimes applied. In contrast, responses in D. simulans were consistent with expectations, demonstrating that this species has selectable genetic variation for the trait. Furthermore, crosses between D. simulans divergent lines showed that the genetic factors involved in grape preference appear to be largely recessive. In summary, our artificial selection study suggests that D. melanogaster and D. simulans possess different genetic architectures for this trait.